Foundations of kinesiology - Oglesby, Carole A.; Henige, Kim; McLaughlin, Douglas W.; Stillwell, Belinda (Burlington, MA Jones & Bartlett Learning, 2018)
"Foundations of Kinesiology is intended for undergraduate kinesiology, physical education, and health science students with an interest in fitness, therapeutic exercise, teaching, coaching, and sport management. Introduction to Kinesiology committed to three core approaches: 1) holistic, 2) learner-centered, and 3) skill development"--Provided by publisher.
Fundamentals and paradoxes -- Pathways to the pillars -- A history of kinesiology -- Biomechanics -- Exercise and sport psychology -- Exercise and sport physiology -- Motor behavior -- Philosophy of kinesiology -- Sport pedagogy and physical activity -- Sociology of sport, exercise, and physical activity -- Adapted physical activity -- Sport management -- Healthy living -- Restoring function -- Discovering possibilities -- Diversity : sport as a welcoming space -- Promoting excellence -- Inclusive physical education for children with autism spectrum disorder -- Kinesiology and the public's health : collaboration imperatives -- Prelude to your career
Includes bibliographical references and index.
Keywords: Kinesiology -- Textbooks; Human mechanics -- Textbooks